Educational innovation in the Basque country: Inclusive equity and European integration - Aramendi Jauregui, Pello (Profesorado, Revista de Currículum y Formación del Profesorado, 2010)
In 2008 the Basque Ministry for Education published a document called “Priority lines for educational innovation” which contained the guidelines for educational innovation in the Basque Autonomous Community. The principles of inclusion, diversity, equity and perspectives for the future are the elements governing the policy for change in the Basque Country. The priority areas promoted by the Government are multiculturalism, multilingualism, school autonomy, coexistence, ICTs, science education and educational quality. The purpose of this article is to describe and analyse the policies developed by the Ministry for Education in the Basque Autonomous Community. The method of research was a mixed (quantitative and qualitative) expost facto study, and data was collected by means of questionnaires, interviews and discussion groups. The sample population included 143 schools providing compulsory education. The results of the research showed that teachers in the Basque Country consider the Government’s action as highly dispersed, not focusing on the more important objectives, and covering too many areas; the teaching staff dissatisfied with the help they receive, they feel the criteria used to select training and innovation projects is not adequate, and, lastly, they claim that the schools should have more autonomy in terms of human resources management. The most innovative schools in the Basque Country are characterised by greater degree of team reflection, having clear rules and guidelines governing working in groups, showing more dedication to the project, better time management, and a higher degree of satisfaction among the teaching staff with support received from the school administration.